HABITAT DAN POPULASI BELIBIS KEMBANG (Dendrocygna arcuata) DI DESA BANGGOI KECAMATAN BULA BARAT KABUPATEN SERAM BAGIAN TIMUR - Monika Rumakey; C. K. Pattinasarany; Lesly Latupapua (Program Studi Manajemen Hutan, Pascasarjana Universitas Pattimura, 2023)
This study aims to determine the Habitat and Population of the Wandering Whistling Duck (Dendrocygna arcuata) in Banggoi Village, West Bula District, East Seram District. This research was conducted using the IPA Method. From the results of the study it turned out that of these three types of habitat, the ones most often used by flower grouse in carrying out activities such as eating, drinking and playing were mostly carried out in swamps. But for the nesting activity of the flower grouse it is usually done in the bushes. Wandering Whistling Duck (D. arcuata), do more activities in the late afternoon and evening, this is because this species is often used as a hunted animal by the community. The population of flower grouse in the study area was found as many as 76 individuals, and more were found in line 3. This was due to the fact that in this research line the main food of the Wandering Whistling Duck (D. arcuata), namely water hyacinth (Eicchornia crassipes) was found.